Etching twin core fiber for the temperature-independent refractive index sensing. (6th March 2018) - Zhang, Chuanbiao; Ning, Tigang; Li, Jing; Zheng, Jingjing; Gao, Xuekai; Lin, Heng; Pei, Li
Abstract: We proposed an ultra-compact chemically etched twin core fiber (TCF) based optic refractive index (RI) sensor, in which the etched fiber was fabricated by immersing in an aqueous solution of hydrofluoric acid (HF) to etch the cladding. Due to the multipath evolutions of light during the TCF, the mode induced interference pattern can be used for measurement. Numerical simulations were performed, demonstrating that only the cladding mode strongly interacts with the surrounding media, and the higher cladding modes will be more sensitive to external medium. In the experiment demonstration, the RI response characteristics of the sensor were investigated, which shows a relatively high RI sensitivity and a much low temperature cross-sensitivity with about 1.06 × 10 −6 RIU °C −1 . Due to low cost and easy fabrication, the sensor can be a suitable candidate in the biochemical field.